2014
DOI: 10.3146/ps13-15.1
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Hand Weeding, Tine and Sweep Cultivation for Weed Control in Organic Peanut Production

Abstract: Previous research has shown that mechanical cultivation is the most effective and affordable method of weed control in organic peanut production. However, growers are in need of more information on specific integrated cultivation regimes for effective season-long weed control with minimal hand-weeding requirements. Therefore, field trials were conducted in 2010–2012 to evaluate the effects of various tine and sweep cultivation treatments combined with or without hand-weeding on season-long weed control, stand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, mechanical weed control is complicated by limitations of equipment design, operation, and cost (Johnson et al 2012b; Johnson and Davis 2015). Mechanical weed control in peanut in the United States is achieved mainly with the use of interrow cultivation implements such as a tine weeder, sweep cultivator, and brush hoe (Johnson et al 2012b; Wann and Tubbs 2014). Weed control using these implements is achieved by cutting, shredding, tearing, and burying weeds (Wann et al 2011).…”
Section: Curative—mechanical Weed Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mechanical weed control is complicated by limitations of equipment design, operation, and cost (Johnson et al 2012b; Johnson and Davis 2015). Mechanical weed control in peanut in the United States is achieved mainly with the use of interrow cultivation implements such as a tine weeder, sweep cultivator, and brush hoe (Johnson et al 2012b; Wann and Tubbs 2014). Weed control using these implements is achieved by cutting, shredding, tearing, and burying weeds (Wann et al 2011).…”
Section: Curative—mechanical Weed Managementmentioning
confidence: 99%
“…], D. ciliaris , J. tamnifolia , R. scabra , and Amaranthus spp. and reduced the hand-weeding time requirement by more than 38% compared with no tine cultivation (Wann and Tubbs 2014). In another study, the control of D. aegyptium , D. ciliaris , D. tortuosum , I. lacunosa , J. tamnifolia , and S. obtusifolia was similar with tine-weeder cultivation of 6- and 8-wk duration (Johnson et al 2012a)…”
Section: Curative—mechanical Weed Managementmentioning
confidence: 99%
“…Organic peanut growers tend to spend more for weed control than conventional peanut growers due to the continued reliance on costly handweeding. This cost is directly related to the time needed to remove weeds by hand; the greater the weed density, the longer it will take and at greater expense (Wann and Tubbs, 2014).…”
Section: Weeds and Their Lossesmentioning
confidence: 99%
“…Furthermore, heavy weed infestations often discourage field workers resulting in sloppy performance or outright abandonment of the work assignment. Research and on-farm demonstrations have shown that handweeding should be viewed as a supplemental tactic that controls escapes, not the primary method of weed control in organic peanut (Wann and Tubbs, 2014).…”
Section: Mechanical Weed Controlmentioning
confidence: 99%
“…The tine weeder is a highspeed and lightweight implement made of series of spring-steel rods arranged in multiple rows that displaces seedling weeds using vibratory action of the tines. Repeated cultivation with a tine weeder effectively controlled annual grasses and small-seeded broadleaf weeds in organic peanut (Johnson and Davis 2015;Johnson et al 2012aJohnson et al , 2012bWann and Tubbs 2014;Wann et al 2011). While the soil surface is thoroughly disturbed to a depth of 1.0 cm by the tine weeder, very little soil is displaced.…”
Section: Introductionmentioning
confidence: 99%